2021
DOI: 10.1017/s0007114521002178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of l-citrulline supplementation on nitric oxide and antioxidant markers after high-intensity interval exercise in young men: a randomised controlled trial

Abstract: L-citrulline (L-Cit) is a nonessential amino acid that stimulates nitric oxide (NO) production and improves exercise performance by reducing muscle damage indices; however, the direct benefits of L-Cit on antioxidant markers are unclear. The aim of this study was to examine antioxidant responses to high-intensity interval exercise following acute L-Cit supplementation. Nine young men (21 ± 1 years) participated in a double-blind crossover study in which they received 12 g of L-Cit and placebo (PL) an hour prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 51 publications
(87 reference statements)
0
21
0
Order By: Relevance
“…Oxidative stress arises when excessive ROS generation surpasses the antioxidant defense systems' buffering capability or when antioxidant enzymes are impaired [6,8]. As a result, high amounts of ROS damage lipids, proteins, DNA and lead to cellular and molecular abnormalities that eventually lead to heart failure [1,2,5,9]. There are two systems against ROS scavenging: Glutaredoxins (Grxs), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) are enzymes, while flavonoids, beta-carotene, vitamins E (Vit E), ascorbic acid (AA), ubiquinone, carotenoids, and lipoic acid are non-enzymatic antioxidants [1,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress arises when excessive ROS generation surpasses the antioxidant defense systems' buffering capability or when antioxidant enzymes are impaired [6,8]. As a result, high amounts of ROS damage lipids, proteins, DNA and lead to cellular and molecular abnormalities that eventually lead to heart failure [1,2,5,9]. There are two systems against ROS scavenging: Glutaredoxins (Grxs), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) are enzymes, while flavonoids, beta-carotene, vitamins E (Vit E), ascorbic acid (AA), ubiquinone, carotenoids, and lipoic acid are non-enzymatic antioxidants [1,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 55 papers were designated for full-text reading. Lastly, seven studies [ 12 , 13 , 14 , 16 , 17 , 18 , 19 ] were included in the qualitative analysis (systematic review). Characteristics of studies included are provided in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the physiological limits of vessel compliance and intact regulatory mechanisms in healthy, active individuals may limit the effects of L-citrulline supplementation on blood flow in more aerobically trained individuals [ 52 ]. Indeed, other studies utilizing L-citrulline paired with high-intensity resistance training have demonstrated increases in NO concentrations [ 16 , 53 ], yet these did not evaluate blood flow during the exercise session.…”
Section: Discussionmentioning
confidence: 99%